Psychological and emotional profiles of Australian uterine transplant potential recipients: A comparison with international trials - Brigitte Gerstl; Eva Kehag; Hayley Mallinder; Tamika Baker; Kaushalya Arulpragasam; Catherine David; Meredith Stone; Elizabeth Fitzsimmons; Kate Hetherington; Rebecca Deans (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Uterus transplant (UTx) has emerged as a groundbreaking solution for individuals with uterine factor infertility (UFI). This study is the first in Australia to explore the psychosocial functioning of potential recipients assessed for the nation's initial UTx clinical trial and to compare their psychological profiles with those from international UTx trials. Material and Methods This is a mixed methods prospective study incorporating standardized psychological measures and semi‐structured interviews. Conducted at a tertiary hospital in Sydney, Australia, the study involved 10 female Australian UTx potential recipients with UFI undergoing assessment for UTx surgery. Participants underwent comprehensive psychological evaluation using validated measures and in‐depth semi‐structured interviews. Quantitative measurement tools included the Hospital Anxiety and Depression Scale, Short Form‐36 Health Survey, Fertility Quality of Life, and the Stanford Integrated Psychosocial Assessment for Transplantation. Thematic analysis was conducted on qualitative data from semi‐structured interviews. Results The Australian UTx potential recipients reported significantly higher Short Form‐36 (SF‐36) scores compared to the Australian general population in general health (p < 0.04), bodily pain (p < 0.02), social functioning (p < 0.02), and emotional well‐being (p < 0.01). Compared with international UTx cohorts, the Australian UTx group showed comparable SF‐36 outcomes, with minor variations observed for general health and physical function domains. Hospital Anxiety and Depression Scale scores revealed lower anxiety, but slightly higher depression levels compared to international UTx trial cohorts. Fertility quality‐of‐life scores were significantly higher in the Australian UTx group compared to women experiencing primary infertility across four domains (p < 0.001). Thematic analysis of interviews highlighted the complex emotional impact of infertility, strong family and social support, and the perception of UTx as a transformative opportunity to achieve wholeness and motherhood. Conclusions UTx represents a novel treatment option for women with UFI. This is the first qualitative study in Australia, it demonstrates the connection between women with UFI and their motivations for parenthood. These findings highlight the importance of tailored psychological assessments and establish a foundation for future research exploring the psychological characteristics of patient candidacy for UTxs.